2011
DOI: 10.1039/c1jm13528g
|View full text |Cite
|
Sign up to set email alerts
|

Uniform dispersion of Pd nanoparticles on carbon nanostructures using a supercritical fluid deposition technique and their catalytic performance towards hydrogen spillover

Abstract: With the aid of supercritical carbon dioxide (scCO 2 ), which has gas-like diffusivity, extremely low viscosity, and near-zero surface tension, highly dispersed Pd nanoparticles (NPs) can be directly synthesized on carbon nanotubes (CNTs). Due to the excellent wettability between scCO 2 and the carbon surface, the deposited Pd NPs are uniformly distributed and tightly anchored on CNTs, which do not require pretreatment. The decoration density of NPs on carbon can be easily regulated by adjusting the Pd(hfa) 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 57 publications
0
52
0
Order By: Relevance
“…The high-strength CNTsa re effective grinding agents that enhance the mixing of Fe and reduce the particle size of the hydride (see Figure S2) whereas the incorporation of CNTsa lso creates microchannels in LiAlH 4 (see Figure S2), and both factors are desirable for the dehydrogenation reaction. [31] As ar esult, ah ierarchical composite catalyst was obtained with intrinsic Fe (~10 nm) and SCCO 2 -deposited Ni nanoparticles (~2nm) on CNTs. [38] Based on the fact that the Fe particles promote the dehydrogenationo fL iAlH 4 ,t his study aims to intentionally decorate the CNTsw ith extra nanoparticles to further improve the performance.…”
Section: Resultsmentioning
confidence: 97%
“…The high-strength CNTsa re effective grinding agents that enhance the mixing of Fe and reduce the particle size of the hydride (see Figure S2) whereas the incorporation of CNTsa lso creates microchannels in LiAlH 4 (see Figure S2), and both factors are desirable for the dehydrogenation reaction. [31] As ar esult, ah ierarchical composite catalyst was obtained with intrinsic Fe (~10 nm) and SCCO 2 -deposited Ni nanoparticles (~2nm) on CNTs. [38] Based on the fact that the Fe particles promote the dehydrogenationo fL iAlH 4 ,t his study aims to intentionally decorate the CNTsw ith extra nanoparticles to further improve the performance.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies [27,28] have shown that MWCNTs are a promising solid state hydrogen storage material. With the proper decoration of transition metal particles, such as Pt and Pd, the MWCNTs could absorb nearly 2.7 wt% of hydrogen under 7 MPa of hydrogen pressure at room temperature via the so-called "spill-over" mechanism.…”
Section: Comparison Between the Effects Of Pt And Pd Decorated Mwcntsmentioning
confidence: 99%
“…The readily accessible supercritical conditions, together with its abundance, low cost, non-flammability, and non-toxicity, have made supercritical carbon dioxide (scCO 2 ) promising for manufacturing various nanosize materials [21][22][23][24][25]. A few investigations showed that the nanoparticles possessed smaller size, narrower size distribution and more homogeneous distribution in the composites synthesized with assistance of scCO 2 , compared with the ones prepared without the assistance of scCO 2 [26][27][28][29].…”
Section: Introductionmentioning
confidence: 97%
“…The composites decorated with nanoparticles with the assistance of scCO 2 exhibit much better properties in applications. Chen et al decorated Pd on carbon nanotubes (CNTs) by oxidative etching using supercritical scCO 2 fluid, resulting in significant increase of the hydrogen storage capacity of CNTs [21].…”
Section: Introductionmentioning
confidence: 99%